2022
DOI: 10.1111/jocs.16882
|View full text |Cite
|
Sign up to set email alerts
|

Median sternotomy pain after cardiac surgery: To block, or not? A systematic review and meta‐analysis

Abstract: Background Inadequate pain control after median sternotomy leads to reduced mobilization, increased respiratory complications, and longer hospital stays. Typically, postoperative pain is controlled by opioid analgesics that may have several adverse effects. Parasternal intercostal block (PSB) has emerged as part of a multimodal strategy to control pain after median sternotomy. However, the effectiveness of this intervention on postoperative pain control and analgesic use has not been fully established. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…This block involves bilateral injections of local anaesthetic in the second to sixth intercostal spaces prior to the placement of sternal wires. [ 3 ] [ Figure 2 ].…”
Section: Regional Analgesiamentioning
confidence: 99%
“…This block involves bilateral injections of local anaesthetic in the second to sixth intercostal spaces prior to the placement of sternal wires. [ 3 ] [ Figure 2 ].…”
Section: Regional Analgesiamentioning
confidence: 99%
“…Parasternal blocks are emerging techniques that can provide targeted pain relief in the anterior thoracic wall, which is commonly incised during cardiac surgery. Among the various parasternal blocks, pecto-intercostal fascial plane block (PIFB) and transversus thoracic plane block (TTP) are commonly used for postoperative pain management following median sternotomy [55]. Additionally, the subcostal transverse abdominal plane block can be used for subxiphoid chest tube coverage in cardiac surgery.…”
Section: Parasternal Blocksmentioning
confidence: 99%
“…Also, an analgesic regimen should be designed to minimize the risk of delirium and facilitate early rehabilitation such as intravenous acetaminophen and a variety of regional anesthesia techniques [5]. A meta-analysis suggested that parasternal nerve block significantly reduced postoperative pain and opioid use [6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, an analgesic regimen should be designed to minimize the risk of delirium and facilitate early rehabilitation such as intravenous acetaminophen and a variety of regional anesthesia techniques [ 5 ]. A meta-analysis suggested that parasternal nerve block significantly reduced postoperative pain and opioid use [ 6 ]. Parasternal plane blocks might significantly improve outcomes for cardiac surgery with sternotomy and should be introduced comprehensively in ERAS protocols [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%